Prevalence of small intestinal bacterial overgrowth in irritable bowel syndrome (IBS): Correlating H2 or CH4 production with severity of IBS. Issue 4 (3rd April 2023) - Onana Ndong, Philippe; Boutallaka, Hanae; Marine‐Barjoan, Eugenia; Ouizeman, Dann; Mroue, Raja; Anty, Rodolphe; Vanbiervliet, Geoffroy; Piche, Thierry
Abstract: Background and Aim: The prevalence and the role of small intestinal bacterial overgrowth (SIBO) in irritable bowel syndrome (IBS) remain unclear, as the literature provides heterogeneous information on the subject. The aim of this study was to determine the prevalence of SIBO in IBS and to assess the correlation between methane and hydrogen levels measured during breath tests and the severity of IBS. Method: Two‐hundred and forty‐seven patients with IBS were prospectively included. A glucose breath test (GBT) measured H2 and CH4 production to diagnose SIBO. A test was positive when H2 values exceeded 12 ppm in the first 90 min and/or when a CH4 value exceeded 10 ppm at any time. IBS severity (IBS‐SSS), quality of life (GIQLI), and anxiety and depression (HAD) were assessed to investigate the correlation with H2 and CH4 production. Results: The prevalence of SIBO in IBS was 36.4% (9.7% with H2, 26.7% with CH4 ). CH4 levels were significantly higher in the predominantly constipated patients ( P  = 0.00), while H2 levels were significantly higher within the diarrheal phenotype ( P  = 0.01). IBS severity was not correlated with either H2 levels ( r  = 0.02; P  = 0.84) or CH4 levels ( r  = 0.05; P  = 0.64). H2 production was inversely correlated with the quality of life ( r  = −0.24; P  = 0.03) and significantly correlated with the HAD scale ( r  = 0.22; P  = 0.03). The pain and discomfort experienced during GBT was not correlated with methane levels ( r  = −0.09, P  = 0.40), hydrogen levels ( r  = −0.01, P  = 0.93), or sum of both ( r  = 0.06, P  = 0.58), but significantly associated with IBS severity ( r  = 0.50, P  <0.00). Conclusion: SIBO has a high prevalence in IBS but does not increase its severity. Individual susceptibility to pain may have a greater influence on the severity of IBS. Abstract : The prevalence of SIBO in this cohort of IBS patients was 36.4%. In IBS patients who tested positive for SIBO, gas levels (hydrogen and methane) measured during glucose breath tests were not correlated with either the severity of IBS symptoms or the level of pain experienced during the test. We found significantly higher values of methan in consitpated patients while hydrogen production was significantly higher in patient with a diarrheal phenotype.